The Second-Generation XPO1 Inhibitor Eltanexor Inhibits Human Cytomegalovirus (HCMV) Replication and Promotes Type I Interferon Response - Liao, Yueyan; Ke, Xiangyu; Deng, Tianyi; Qin, Qingsong (Frontiers in Microbiology, 2021)
Human cytomegalovirus (HCMV) is a ubiquitous opportunistic pathogen and can be life-threatening for immunocompromised individuals. There is currently no available vaccine for the prevention of HCMV- associated diseases and most of the available antiviral drugs that target viral DNA synthesis become ineffective in treating HCMV mutants that arise after long-term use in immunocompromised patients. Here, we examined the effects of Eltanexor, a second-generation selective inhibitor of nuclear export (SINE), on HCMV replication. Eltanexor effectively inhibits HCMV replication in human foreskin fibroblasts in a dose-dependent manner. Eltanexor does not significantly inhibit viral entry and nuclear import of viral genomic DNA, but rather suppress the transcript and protein levels of viral immediate-early (IE), early (E) and late (L) genes, and abolishes the production of infectious virions. We further found Eltanexor treatment promotes proteasome-mediated degradation of XPO1, which contributes to the nuclear retention of interferon regulatory factor 3 (IRF-3), resulting in increased expression of type I interferon as well as interferon stimulating genes ISG15 and ISG54. This study reveals a novel antiviral mechanism of Eltanexor which suggests it has potential to inhibit a broad spectrum of viral pathogens.